Gender analysis of the hive product value chain in Benin - Vodounou, G. Kéty; SOSSOU, KOFFI BENOÎT; Attanasso, Marie-Odile (My University, 2022)
The purpose of this study is to identify the role of gender throughout the hive product value chain in Benin. The data is collected through a socio-economic survey. A total of 430 beekeepers, including 43 women, were surveyed using the snowball method. Macro, meso and micro level analyses of the said chain were carried out followed by a SWOT analysis. Data processing was done with Excel 2016, SPSS, and ARCGIS 10.1 software. The results of the study indicated that women beekeepers intervene more at the level of honey extraction with a participation rate of about half and a participation rate of less than 20% in the other links of the chain. While the men occupy more remunerative segments as the marketing, the production, the harvest of the honey as well as the manufacture of the wax. Three types of beekeeping groups were identified: men's, women's and mixed groups.
Keywords: Gender; value chain; beekeeping; honey; Benin